2013
DOI: 10.1111/1567-1364.12121
|View full text |Cite
|
Sign up to set email alerts
|

Human ribosomal protein L9 is a Bax suppressor that promotes cell survival in yeast

Abstract: The identification of a human ribosomal protein L9 (hRPL9) cDNA as a sequence capable of suppressing the lethal effects of heterologously expressed murine Bax in yeast led us to investigate its antiapoptotic potential. Using growth and viability assays, we show that yeast cells heterologously expressing hRPL9 are resistant to the growth inhibitory and lethal effects of exogenously supplied copper, indicating that it has pro-survival properties. To explore potential mechanisms, we used yeast mutants defective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…In order to determine whether TC-1 could protect against other stressors besides Bax, cell-death-inducing levels of copper sulfate were used 59. Using the spot assay with increasing concentrations of copper sulfate, the cells harbouring only the vector show reduced growth, while cells harbouring TC-1 and 14-3-3 expressing plasmids remain largely unaffected (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to determine whether TC-1 could protect against other stressors besides Bax, cell-death-inducing levels of copper sulfate were used 59. Using the spot assay with increasing concentrations of copper sulfate, the cells harbouring only the vector show reduced growth, while cells harbouring TC-1 and 14-3-3 expressing plasmids remain largely unaffected (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Sub-lethal level of a mild stress is often required to activate over-expressed native pro-apoptotic proteins for them to induce cell death. Here we used copper sulfate at a concentration that is known to be sub-lethal 59. Cultures of yeast doubly transformed with different combinations of expression vectors, including empty vectors, pro-apoptotic genes and TC-1 or 14-3-3 were serially diluted and spotted on nutrient agar media containing galactose alone or with sub-lethal copper sulfate (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that RPL3 over-expression caused an increase in its aberrantly spliced mRNA, which was degraded by the nonsense-mediated decay pathway (Malygin et al, 2007). Moreover, RPL3 might play an important role in silencing the human embryonic epsilon-globin gene expression (Huang et al, 2000), and its over-expression led to growth inhibition (Eid et al, 2013). Strong down-regulation of the steady state mRNA level of RPL3 was observed upon induction of differentiation in HL-60 cells (Mailhammer et al, 1992).…”
Section: Discussionmentioning
confidence: 99%